Cultural aspects as a root cause of organizational failure in risk and crisis management in the Fukushima Daiichi disaster. (March 2021) - Murata, Atsuo
Highlights: We discussed the reason why an organizational failure in risk and crisis management occurred. This was discussed from the viewpoints of groupism. This was also discussed from obedience to authority and willful blindness. Abstract: This study explores root causes of the Fukushima Daiichi disaster and discusses how an urgent situation, such as a station blackout (SBO), should be addressed on an organizational and managerial level so that future disasters may be prevented. First, based on the summary of the literature on this disaster, the malfunctions and troubles of facilities that caused the disaster are extracted. Second, it is verified that these malfunctions were caused by failures of organizational risk and crisis management. Third, we discuss the reason why an organizational failure in risk and crisis management occurred from the viewpoints of cultural aspects such as groupism ("Wa"), obedience to authority, willful blindness, open safety culture, and just culture.